Addressing Tobacco Use to Reduce Cardiovascular Disease - Mosley, Mary (MD Conference Express, 2013)
This article reviews the scope of the impact of tobacco on cardiovascular disease (CVD) and its mode of action, the lack of awareness of physicians about smoking cessation tactics, and smoking cessation as a treatment for CVD.